2019
DOI: 10.1111/jpi.12544
|View full text |Cite
|
Sign up to set email alerts
|

Sleep well. Untangling the role of melatonin MT1 and MT2 receptors in sleep

Abstract: The pharmacological potential of targeting selectively melatonin MT1 or MT2 receptors has not yet been exploited in medicine. Research using selective MT1/MT2 receptor ligands and MT1/MT2 receptor knockout mice has indicated that the activation of MT2 receptors selectively increases non‐rapid eye movement (NREM) sleep whereas MT1 receptors seem mostly implicated in the regulation of REM sleep. Moreover, MT1 knockout mice show an increase in NREM sleep, while MT2 knockout a decrease, suggesting an opposite role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 25 publications
3
32
1
Order By: Relevance
“…39 Finally, MLT MT 2 receptors are strongly involved in the regulation of the sleep/wake cycle. 16,17 MT 2 was found to be highly expressed in the VLPO and less in the SCN, 18 further supporting our hypothesis that MLT rescued the prolonged period length caused by NMDAR impairment through the homeostatic system. However, since MLT MT 2 receptors have been found expressed in other brain regions involved in the regulation of sleep and arousal, 16 such as the reticular thalamus, further research should investigate the contribution of these regions in the therapeutic effects of MLT over MK-801-induced impairments.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…39 Finally, MLT MT 2 receptors are strongly involved in the regulation of the sleep/wake cycle. 16,17 MT 2 was found to be highly expressed in the VLPO and less in the SCN, 18 further supporting our hypothesis that MLT rescued the prolonged period length caused by NMDAR impairment through the homeostatic system. However, since MLT MT 2 receptors have been found expressed in other brain regions involved in the regulation of sleep and arousal, 16 such as the reticular thalamus, further research should investigate the contribution of these regions in the therapeutic effects of MLT over MK-801-induced impairments.…”
Section: Discussionsupporting
confidence: 78%
“…15 Melatonin (MLT) is an endogenous hormone produced by the pineal gland that acts through two G-protein coupled receptors, named melatonin MT 1 and melatonin MT 2 , that seem to be attractive candidates to treat sleep disorders. 16,17 The effect of MLT on sleep is still debated and mostly seems to affect sleep latency; one of the hypotheses is that MLT promotes sleep through entraining or phase shifting the circadian clock since MT 1 and MT 2 receptors have been reported in the SCN. 18,19 Another hypotheses is that MLT can modulate the homeostatic sleep process, in particular NREM sleep, by acting on MLT MT 2 receptors expressed in brain areas implicated in NREM sleep including the reticular thalamus and the ventrolateral preoptic area.…”
Section: Introductionmentioning
confidence: 99%
“…The onset of nighttime melatonin secretion is initiated approximately 2 h in advance of an individual's habitual bedtime and has been shown to correlate with the onset of evening sleepiness. Several studies implicate endogenous melatonin in the physiological regulation of the circadian mechanisms governing sleep propensity [27,28]. Aging often is associated with a significant reduction in sleep efficiency and continuity and coincides with a significant reduction in amplitude of the melatonin rhythm and consequently of many other circadian rhythms as well [29].…”
Section: Sleep Alteration During Agingmentioning
confidence: 99%
“…This could be explained by the very short half-life of melatonin and also by the contrasting/complementary role of melatonin receptors on sleep phases. Preclinical studies showed that MT1 selective stimulation increased rapid eye movement (REM) sleep while MT2 receptors increased non-rapid eye movement www.nature.com/scientificreports www.nature.com/scientificreports/ (NREM) sleep highlighting an opposite role of both receptors 56 . Further research investigating melatonergic receptors and different ligands is needed in order to clarify the specific role of each ligand.…”
Section: Discussionmentioning
confidence: 99%